Comparison of the Gravimetric Network in Esfarayen Region with the Network of Fractal Analysis - Mohsenlo, Alireza; Teymoorian, Asghar; Maanijou, Mohammad (International Journal of Geography and Geology, 2016)
The place of gravity stations is normally irregularly distributed. Although an ideal arrangement should be locally homogeneous, it is impossible in most cases, due to the availability issues. The surface areas due to more geological benefits and easier availability are more densely sampled which inevitably affects the measurement of the regular network as the interpolation error due to irregular distribution. The gravimetric data are usually presented by the color contour maps and it is required to be interpolated as a regular network. The combined distribution of the gravity stations are used in theoretical studies. It was found that there is an interval of the values for the random distribution of the data which has 2 fractal dimension dependent on Euclidean geometry for the spatial distribution of the data. And a new Bouguer was found using the grid and using anomaly fractal analysis in Esfarayen area gained, based on which a closer analysis of the explored area was conducted. The important anomaly in the region was recreated. Using the related fractal analysis reduces the number of data mined points.